A naturally protective epitope of limited variability as an influenza vaccine target - Craig P. Thompson (Nature Portfolio, 2018)
Current influenza vaccine approaches largely focus on highly variable epitopes with high immunogenicity or epitopes of low variability that often have low immunogenicity. Here, Thompson et al. identify a highly immunogenic epitope of limited variability in the head domain of the H1 haemagglutinin and show protection from diverse H1N1 strains in mice.